Shift of Neutrophils From Blood to Bone Marrow Upon Extensive Experimental Trauma Surgery - Teuben, Michel P. J.; Heeres, Marjolein; Blokhuis, Taco; Spijkerman, Roy; Knot, Eric; Vrisekoop, Nienke; Pfeifer, Roman; Pape, Hans-Christoph; Koenderman, Leo; Leenen, Luke P. H. (Frontiers in Immunology, 2022)
INTRODUCTION: Extensive trauma surgery evokes an immediate cellular immune response including altered circulatory neutrophil numbers. The concurrent bone marrow (BM) response however is currently unclear. We hypothesize that these BM changes include (1) a relative reduction of the bone marrow neutrophil fraction and (2) increasing heterogeneity of the bone marrow neutrophil pool due to (3) the appearance of aged/returning neutrophils from circulation into the BM-compartment. MATERIAL AND METHODS Eight pigs were included in a standardized extensive trauma surgery model. Blood and bone marrow samples were collected at baseline and after 3 hours of ongoing trauma surgery. Leukocyte and subtype counts and cell surface receptor expression levels were studied by flow cytometry. RESULTS All animals survived the interventions. A significant drop in circulating neutrophil counts from 9.3 to 3.2x106 cells/ml (P=0.001) occurred after intervention, whereas circulatory neutrophil cell surface expression of CD11b increased. The concurrent bone marrow response included an increase of the BM neutrophil fraction from 63 ± 3 to 71 ± 3 percent (P<0.05). Simultaneously, the BM neutrophil pool became increasingly mature with a relative increase of a CXCR4high-neutrophil subtype that was virtually absent at baseline. CONCLUSION The current study shows a shift in composition of the BM neutrophil pool during extensive trauma surgery that was associated with a relatively circulatory neutropenia. More specifically, under these conditions BM neutrophils were more mature than under homeostatic conditions and a CXCR4high-neutrophil subset became overrepresented possibly reflecting remigration of aged neutrophils to the BM. These findings may contribute to the development of novel interventions aimed to modify the trauma-induced immune response in the BM.